2019
DOI: 10.3390/ijms20030767
|View full text |Cite
|
Sign up to set email alerts
|

MIST1, an Inductive Signal for Salivary Amylase in Mesenchymal Stem Cells

Abstract: Sjögren’s syndrome (SjS) is an autoimmune disease that destroys the salivary glands and results in severe dry mouth. Mesenchymal stem cell (MSC) transplantation has been recently proposed as a promising therapy for restoring cells in multiple degenerative diseases. We have recently utilized advanced proteomics biochemical assays to identify the key molecules involved in the mesenchymal-epithelial transition (MET) of co-cultured mouse bone-marrow-derived MSCs mMSCs with primary salivary gland cells. Among the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…[41] Furthermore, the MIST-1 signal has been reported to enhance the expression of salivary amylase 1 in vitro . [42]…”
Section: Kindsmentioning
confidence: 99%
“…[41] Furthermore, the MIST-1 signal has been reported to enhance the expression of salivary amylase 1 in vitro . [42]…”
Section: Kindsmentioning
confidence: 99%
“…FN1, in addition to collagen I and II, upregulated in pancreatic exocrine acinar cells corresponding to the overexpression of a protein named muscle, intestine and stomach expression 1 (MIST-1) [42]. It is important to note that our previous study revealed that MIST-1, a basic helix-loop-helix transcription factor for AMY1 expression, was upregulated in co-cultured MSCs [25,26,43]. Additionally, MIST1 was found to be an upstream key regulator of FN1 [44] and other transcription factors like TCF3 [45] and PTF1A [46].…”
Section: Discussionmentioning
confidence: 96%
“…Expression of the M3 receptor was detected at both the mRNA and protein level in mouse BM-MSCs [58]. The M3 receptor was localised primarily to the endoplasmic reticulum in the investigated BM-MSCs and as such were not competent to signal.…”
Section: Expression Of Of Machrs In Mscsmentioning
confidence: 90%